EFFECT OF WORK MOTIVATION, COMMUNICATION, AND TRAINING ON EMPLOYEE PERFORMANCE AT PT. PARAMA TIRTA MULYA SEJAHTERAH - yona, mira; mutiara, jeffi (Ekspektra : Jurnal Bisnis dan Manajemen, 2020)
This study aims to determine the effect of work motivation, work communication and job training on the performance of  PT Parama Tirta Mulya Sejahterah employees. Both partially and simultaneously. The type of this research is quantitative research. The population of this study is all employees of PT. 43 employees. Sampling technique is done by saturated sampling technique. Data is obtained using a questionnaire (questionnaire) that is tested for validity and reliability. The results of data analysis found that there was a positive influence between motivation on employee performance with the coefficient value b1 = 0.452. There was a positive influence between work communication on employee performance with a coefficient value of b2 = 0.038. There was a positive influence between training )on employee performance with a coefficient value of b3 = 0.333. There was a significant positive effect of employee performance, Partial Test Results (t-test) between work motivation with work performance wan shows the value of t-count greater than t-table (3,829> 2,601), between communication and employee performance shows the value of t-count greater than t-table value (2,808> 2,016), and between training and employee performance shows the value of t-count greater than t-table value (2,213> 2,016), this shows that there is a significant positive effect partially. The result of the calculated F value is 44.981 and the probability of significance is 0.000.